Implementasi Algoritme SPECK Pada Proses Pengiriman File Multimedia Melalui Jaringan Internet - David Christanto; Ari Kusyanti; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Audio recording is one of the multimedia files that are often encountered today. One example is the sound recording that can be used as evidence in the trial of the law. The proof of sound recording is supported by UU No 11 Tahun 2008 Pasal 5 ayat 1 regarding information and electronic transactions that stated :